A hard alloy component and its preparation method, and machine tool

By making the hard phase and the bonded phase change in the setting direction in a cemented carbide component, combined with 3D printing technology, the problem that it is difficult for cemented carbide components to have high hardness and high toughness at the same time is solved, and high hardness and high toughness are achieved The "double-high" mechanical properties of toughness are suitable for the manufacturing of mechanical tools.

CN112605386BActive Publication Date: 2024-12-27GUANGDONG INST OF NEW MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202011554469.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2024-12-27
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Existing cemented carbide parts are difficult to have high hardness and high toughness at the same time, and cannot meet the diverse performance requirements at different locations.

Method used

The hard carbide parts are prepared by 3D printing technology. By making the hard phase and the bonded phase change in the setting direction in at least two hard carbide layers, the hard phase content is between 20-90 wt%, and the bonded phase content is between 80- The porosity of each layer is less than 0.02%, and sintered at 1280-1480°C.

Benefits of technology

The high hardness and high toughness of cemented carbide parts are achieved, the "double high" mechanical properties are reduced, the requirements of 3D printing technology for powder morphology and fluidity are reduced, and the hardness and toughness of mechanical tools are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112605386B_ABST
    Figure CN112605386B_ABST
Patent Text Reader

Abstract

The present invention discloses a cemented carbide component and a preparation method thereof, and a mechanical tool, and belongs to the field of 3D printing technology. The cemented carbide component has at least two layers of cemented carbide layers, each of which contains a hard phase and a bonding phase at the same time, and the hard phase and the bonding phase in at least two layers of cemented carbide layers are respectively gradient-changed along the setting direction of the cemented carbide layers. By making the brittle and tough phases in the cemented carbide component spatially distributed in a gradient, the mechanical properties with gradient changes are obtained accordingly, so that the cemented carbide component has "double high" mechanical properties of high hardness and high toughness. It is obtained by sintering a cemented carbide component blank formed by 3D printing. The method is simple and easy to operate. It is used in mechanical tools, such as cutting tools, geological mining tools or wear-resistant parts, to improve the hardness and toughness of the mechanical tools.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing, and in particular to a cemented carbide component and a preparation method thereof, and a machine tool. Background Art

[0002] Cemented carbide materials are composite materials composed of refractory metal hard compounds and bonding metals / alloys, which can be used to manufacture cutting tools, geological and mining tools, molds and wear-resistant parts. Cemented carbide parts are used in harsh service environments and often have different performance requirements at different locations. For example, the surface of geological and mining tools requires high hardness and high wear resistance, while the core must have high bending strength and fracture toughness to resist excavation impact.

[0003] At present, the main preparation methods of cemented carbide parts include powder metallurgy, melt infiltration and powder combustion synthesis, but it is difficult for cemented carbide parts made by these methods to have high hardness and toughness at the same time.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention includes providing a cemented carbide component having "double high" mechanical properties of high hardness and high toughness.

[0006] The second object of the present invention includes providing a method for preparing the above-mentioned cemented carbide component.

[0007] A third object of the present invention includes providing a machine tool comprising the above-mentioned cemented carbide component.

[0008] This application can be implemented as follows:

[0009] In the first aspect, the present application provides a cemented carbide component having at least two cemented carbide layers, each of which contains both a hard phase and a bonding phase, and the hard phase and the bonding phase in the at least two cemented carbide layers respectively change in a gradient along the setting direction of the cemented carbide layers.

[0010] In an optional embodiment, along the setting direction, the content of the hard phase changes gradually within the range of 20-90wt%, and the content of the bonding phase changes gradually within the range of 80-10wt%.

[0011] In an alternative embodiment, the hard phase is formed of a refractory metal hard compound, and the bonding phase is formed of a bonding metal or a bonding alloy.

[0012] In an optional embodiment, the refractory metal hard compound is at least one of TiC, WC, Ti(C,N) and Cr3C2.

[0013] In an alternative embodiment, the bonding metal includes at least one of Ni, Mo, Co, Fe and alloys thereof.

[0014] In an optional embodiment, the porosity of each cemented carbide layer is less than 0.02%.

[0015] In an optional embodiment, the number of cemented carbide layers is 3, and the 3 cemented carbide layers are arranged in sequence from bottom to top.

[0016] In an optional embodiment, the thickness of each cemented carbide layer is not less than 0.2 mm.

[0017] In an optional embodiment, the thickness of the first hard alloy layer at the bottom is 28-32 mm, the thickness of the third hard alloy layer at the top is 68-72 mm, and the thickness of the second hard alloy layer between the first and third hard alloy layers is 74-76 mm.

[0018] In an optional embodiment, the number of cemented carbide layers is 2, and the two cemented carbide layers are arranged in sequence from the inside to the outside.

[0019] In an optional embodiment, the width of the first hard alloy layer located in the inner layer is 68-70 mm; the thickness of the second hard alloy layer located in the outer layer is 0.15-0.25 mm.

[0020] In a second aspect, the present application provides a method for preparing a cemented carbide component according to any of the aforementioned embodiments, which is obtained by sintering a 3D printed cemented carbide component blank.

[0021] In an optional embodiment, the cemented carbide component blank is obtained by the following method:

[0022] According to the 3D printing data, cemented carbide suspension slurry containing different contents of hard phase is spray-deposited, and ultraviolet light irradiation is used during the spray-deposition process.

[0023] In an optional embodiment, the cemented carbide suspension slurry contains, by volume percentage, 50-62% cemented carbide powder, 15-20% photosensitive resin, 10-15% active diluent, 2-5% photoinitiator, 5-10% solvent, 0.5-2% dispersant and 0.1-0.5% defoaming agent.

[0024] In an alternative embodiment, the cemented carbide powder contains 20-90 wt % of a refractory metal hard compound, with the remainder being a binder metal or a binder alloy.

[0025] In an alternative embodiment, the particle size of the cemented carbide powder is 2-40 μm.

[0026] In an alternative embodiment, the photosensitive resin includes at least one of epoxy acrylate resin, bisphenol A epoxy acrylate, and polyurethane acrylate.

[0027] In an optional embodiment, the reactive diluent includes at least one of dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, and tripropylene glycol diacrylate.

[0028] In an optional embodiment, the photoinitiator includes at least one of 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-2-methylphenylacetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and isooctyl p-N,N-dimethylaminobenzoate.

[0029] In an optional embodiment, the solvent includes at least one of acetone, ethanol, and chloroform.

[0030] In an optional embodiment, the dispersant includes at least one of oleic acid, DP310 polymer dispersant and EFKA-5064 dispersant.

[0031] In an optional embodiment, the defoaming agent includes at least one of n-butanol and polyether-modified silicone oil.

[0032] In an optional embodiment, the sintering is performed at 1280-1480°C.

[0033] In an optional embodiment, before sintering, the cemented carbide component blank is also degreased.

[0034] In an optional embodiment, the degreasing is carried out under a protective atmosphere at 400-800° C. for 1-4 hours.

[0035] In an optional embodiment, before degreasing, the cemented carbide component blank is also dried.

[0036] In an alternative embodiment, the drying is performed at 40-80°C.

[0037] In a third aspect, the present application provides a machine tool comprising a cemented carbide component according to any one of the aforementioned embodiments.

[0038] In an optional embodiment, the machine tool comprises a cutting tool, a geological mining tool or a wear-resistant part.

[0039] The beneficial effects of this application include:

[0040] The present application achieves gradient distribution of the brittle and tough phases in cemented carbide parts in space, and accordingly obtains gradient-varying mechanical properties, thereby making the cemented carbide parts have "double high" mechanical properties of high hardness and high toughness.

[0041] This cemented carbide component is obtained by sintering the 3D printed cemented carbide component blank. While maintaining the free forming ability, 100% material utilization rate and rapid forming characteristics of 3D printing technology, it can greatly reduce the requirements of 3D printing technology on powder morphology and fluidity, and realize the optimal design and low-cost printing of "double high" performance gradient structure cemented carbide components.

[0042] The cemented carbide parts obtained in this way are used to process machine tools, such as cutting tools or geological mining tools, etc., which can improve the hardness and toughness of machine tools. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 The following is a flow chart of the preparation process of the high manganese steel bonded hard alloy with gradient structure in Example 1. Figure 1 (a) shows the preparation process of high manganese steel bonded cemented carbide suspension slurry, Figure 1 (b) Represents the design process of the three-dimensional model of the gradient structure; Figure 1 (c) shows the multi-nozzle 3D printing process; Figure 1 (d) represents the drying process, Figure 1 (e) shows the debinding sintering process.

[0045] Figure 2 This is a three-dimensional model of the part in Example 1 in which the TiC content is distributed in the range of 40wt%-30wt%-20wt%.

[0046] Figure 3 This is the spatial gradient distribution diagram of TiC (hard phase) in the sintered sample of Example 1.

[0047] Figure 4 1 and 2 are XRD curves of different regions of the sintered sample of Example 1.

[0048] Figure 5 This is a graph showing the hardness change of the sintered sample of Example 1.

[0049] Figure 6 This is a graph showing changes in flexural strength and impact toughness of the sintered sample of Example 1.

[0050] Figure 7This is a diagram of the printed gradient structure carbide gear in Example 2.

[0051] Figure 8 This is the microstructure diagram of the cemented carbide gear with gradient structure in Example 2.

[0052] Fig. 9 This is a graph showing the density and hardness changes of the cemented carbide gear with a gradient structure in Example 2.

[0053] Fig.10 This is the microstructure diagram of the cemented carbide prepared by the traditional powder metallurgy method in Comparative Example 1.

[0054] Fig.11 This is the microstructure diagram of the unsintered dense cemented carbide component in Comparative Example 2.

[0055] Icons: 1- cemented carbide suspension slurry feeding system; 2- multi-nozzle printing system; 3- ultraviolet light generator; 4- gradient structure steel bonded cemented carbide part blank; 5-40wt% TiC alloy layer; 6-30wt% TiC alloy layer; 7-20wt% TiC alloy layer; 8-20wt% WC-Co high toughness layer; 9-90wt% WC-Co hard wear-resistant layer. DETAILED DESCRIPTION

[0056] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0057] The cemented carbide parts and their preparation methods and machine tools provided in this application are described in detail below.

[0058] The present application proposes a cemented carbide component having at least two cemented carbide layers, each of which contains both a hard phase and a bonding phase, and the hard phase and the bonding phase in the at least two cemented carbide layers change in a gradient along the setting direction of the cemented carbide layers.

[0059] For reference, along the setting direction, the content of the hard phase can change in a gradient within the range of 20-90wt%, which can be understood as a gradient increase or a gradient decrease, and each gradient can differ by 1wt%, 2wt%, 5wt% or 10wt%, etc. Correspondingly, the content of the bonding phase changes in a gradient within the range of 80-10wt%, which can be understood as a gradient decrease or a gradient increase, and each gradient can differ by 1wt%, 2wt%, 5wt% or 10wt%, etc. The sum of the content of the hard phase and the content of the bonding phase is 100wt%, that is, the content of the hard phase continues to increase, and correspondingly, the content of the bonding phase continues to decrease.

[0060] The hard phase is composed of refractory metal hard compounds, such as TiC. In addition, the refractory metal hard compounds can also be WC, Ti(C,N) or Cr3C2, etc. In addition, it can also contain two or more of the above substances.

[0061] The bonding phase is formed of a bonding metal or a bonding alloy. In an optional embodiment, the bonding metal includes at least one of Ni, Mo, Co, Fe and alloys thereof.

[0062] By making the brittle and tough phases in the cemented carbide parts have a gradient distribution in space, the mechanical properties with gradient changes are obtained accordingly, so that the cemented carbide parts have "double high" mechanical properties of high hardness and high toughness. In addition, in view of the composition of the above-mentioned hard phase and bonding phase, the cemented carbide parts also have the characteristics of high hardness, high wear resistance, high hardness, high elastic modulus, good chemical stability and small thermal expansion coefficient.

[0063] For reference, in the cemented carbide component provided in the present application, the porosity of each cemented carbide layer is less than 0.02%, so that the entire cemented carbide component is nearly fully dense, thereby improving the hardness of the cemented carbide component.

[0064] In some embodiments, the number of cemented carbide layers is 3, and the 3 cemented carbide layers are arranged sequentially from bottom to top, that is, deposited layer by layer from bottom to top during the 3D printing process. For reference, the thickness of each cemented carbide layer is not less than 0.2 mm to ensure the formation of a macroscopic gradient structure cemented carbide layer.

[0065] In some embodiments, the thickness of the first cemented carbide layer at the bottom is 28-32 mm, such as 28 mm, 29 mm, 30 mm, 31 mm or 32 mm, etc. The thickness of the third cemented carbide layer at the top is 68-72 mm, such as 68 mm, 69 mm, 70 mm, 71 mm or 72 mm, etc. The thickness of the second cemented carbide layer between the first cemented carbide layer and the third cemented carbide layer is 74-76 mm, such as 74 mm, 75 mm or 76 mm, etc.

[0066] In some other embodiments, the number of hard alloy layers is 2, and the two hard alloy layers are arranged from the inside to the outside, that is, they are sprayed from the inside to the outside during the 3D spraying process.

[0067] In some embodiments, the width of the first cemented carbide layer located in the inner layer is 68-70 mm, such as 68 mm, 69 mm or 70 mm, etc. The thickness of the second cemented carbide layer located in the outer layer is 0.15-0.25 mm, such as 0.15 mm, 0.2 mm or 0.25 mm, etc.

[0068] In other embodiments, the number of cemented carbide layers may be 4, 5, 10 or more.

[0069] In addition, the present application also provides a method for preparing the above-mentioned cemented carbide component, which is obtained by sintering a 3D-printed cemented carbide component blank. 3D printing technology can better regulate the distribution and arrangement of the hard phase.

[0070] In an optional embodiment, the cemented carbide component blank can be obtained in the following manner: according to 3D printing data, cemented carbide suspension slurry containing different contents of hard phase is spray-deposited, and ultraviolet light is irradiated during the spray-deposition process.

[0071] Spray deposition can be performed using a multi-nozzle 3D printing device. The printing device can be equipped with more than two micro-screw extrusion print heads and a UV generator. Multiple print heads are used to selectively spray and deposit a variety of suspended slurries with different hard phase contents layer by layer, and cross-link and solidify them under the action of ultraviolet light, so as to achieve directional regulation of the gradient distribution of cemented carbide hard phase and bonding phase in space, and print out a cemented carbide component blank with a gradient structure.

[0072] In this process, the content of hard phase in the cemented carbide suspension slurry used in each layer is different, that is, along the 3D printing direction, the content of hard phase (refractory metal hard compound) in cemented carbide parts changes gradiently within its range, and the bonding phase (bonding metal or bonding alloy) also changes gradiently within its range.

[0073] In an optional embodiment, the cemented carbide suspension slurry contains, by volume percentage, 50-62% cemented carbide powder, 15-20% photosensitive resin, 10-15% active diluent, 2-5% photoinitiator, 5-10% solvent, 0.5-2% dispersant and 0.1-0.5% defoaming agent.

[0074] For reference, the volume content of the cemented carbide powder can be 50%, 52%, 55%, 58%, 60% or 62%, etc., or any other value within the range of 50-62%.

[0075] The volume content of the photosensitive resin may be 15%, 16%, 17%, 18%, 19% or 20%, etc., or any other value within the range of 15-20%.

[0076] The volume content of the active diluent can be 10%, 11%, 12%, 13%, 14% or 15%, etc., or any other value within the range of 10-15%.

[0077] The volume content of the photoinitiator can be 2%, 3%, 4% or 5%, etc., or any other value within the range of 2-5%.

[0078] The volume content of the solvent may be 5%, 6%, 7%, 8%, 9% or 10%, etc., or any other value within the range of 5-10%.

[0079] The volume content of the dispersant may be 0.5%, 1%, 1.5% or 2%, etc., or any other value within the range of 0.5-2%.

[0080] The volume content of the defoaming agent can be 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc., or any other value within the range of 0.1-0.5%.

[0081] It is worth noting that the above components can be freely combined within their respective ranges, and of course, the total must satisfy 100%.

[0082] The cemented carbide powder contains 20-90wt% (such as 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%) of refractory metal hard compound, and the remainder is bonding metal or bonding alloy. The particle size of the cemented carbide powder is 2-40μm (such as 2μm, 5μm, 10μm, 20μm, 30μm or 40μm).

[0083] The photosensitive resin may include at least one of epoxy acrylate resin, bisphenol A epoxy acrylate and polyurethane acrylate. The reactive diluent may include at least one of dipropylene glycol diacrylate, 1,6-hexanediol diacrylate and tripropylene glycol diacrylate. The photoinitiator may include at least one of 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl)butanone, 2-hydroxy-2-methylphenylacetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and p-N,N-dimethylaminobenzoic acid isooctyl ester. The solvent may include at least one of acetone, ethanol and chloroform. The dispersant may include at least one of oleic acid, DP310 polymer dispersant and EFKA-5064 dispersant. The defoamer may include at least one of n-butanol and polyether-modified silicone oil.

[0084] The reaction mechanism of the above substances is: the photoinitiator in the suspension slurry with different hard phase contents absorbs ultraviolet light to generate active free radicals, which trigger the polymerization reaction of the photosensitive resin and the active diluent to generate a network polymer that covers and fixes the cemented carbide powder, so that the cemented carbide suspension slurry is solidified and formed. By adjusting the concentration of the active diluent, the curing speed of the cemented carbide suspension slurry can be controlled to be suitable for multi-nozzle 3D printing.

[0085] The above technology is based on the discrete-superposition principle, and realizes the manufacture of complex three-dimensional entities by stacking materials layer by layer. This method combines the flexible manufacturing capabilities of 3D printing technology, the excellent performance of cemented carbide materials, and the designability of its composition and structure to achieve the optimization of product structure, shape and performance.

[0086] In the present application, sintering can be carried out at 1280-1480°C (such as 1280°C, 1300°C, 1350°C, 1400°C, 1450°C or 1480°C, etc.). It is worth noting that when sintering is carried out at a temperature lower than 1280°C, a dense gradient structure cemented carbide component cannot be obtained, and the cemented carbide component contains a large number of pores. When sintering is carried out at a temperature higher than 1480°C, it will cause problems such as volatilization of the bonding metal and decarburization and decomposition of the refractory metal hard compound, resulting in an increase in the porosity of the cemented carbide component and a decrease in performance.

[0087] In an optional embodiment, before sintering, the cemented carbide component blank is further degreased. For reference, the degreasing can be carried out under a protective atmosphere at 400-800°C (such as 400°C, 500°C, 600°C, 700°C or 800°C) for 1-4h (such as 1h, 2h, 3h or 4h).

[0088] Furthermore, before degreasing, the hard alloy component blank is dried. The drying can be performed at 40-80°C (such as 40°C, 50°C, 60°C, 70°C or 80°C).

[0089] Specifically, the preparation process can refer to:

[0090] (1) preparing a plurality of cemented carbide suspension slurries with different hard phase contents: 50-62 vol% cemented carbide powder with different hard phase contents, 15-20 vol% photosensitive resin epoxy acrylate, 10-15 vol% active diluent dipropylene glycol diacrylate, 2-5 vol% photoinitiator 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 5-10 vol% solvent acetone, 0.5-2 vol% dispersant oleic acid and 0.1-0.5 vol% defoamer n-butanol, preparing cemented carbide suspension slurries with different hard phase contents, good rheology and controllable curing as raw materials for 3D printing;

[0091] The cemented carbide powder has a particle size of 2-40 μm and is composed of 20-90 wt% of refractory metal hard compound (hard phase) and 10-80 wt% of bonding metal / alloy (bonding phase).

[0092] (2) Three-dimensional modeling of cemented carbide parts with gradient structures: According to the service requirements of cemented carbide parts, a three-dimensional model of cemented carbide parts with gradient structures is designed and constructed. The linear dimensions of the three-dimensional model are enlarged by 115-130%, and layered and sliced ​​to generate printing data.

[0093] (3) Multi-nozzle 3D printing: Based on the three-dimensional model printing data of cemented carbide parts, a multi-nozzle 3D printing system is used to selectively and alternately print cemented carbide suspension slurries with different hard phase contents layer by layer, and ultraviolet light is used to induce the polymerization and curing of the photosensitive resin in the cemented carbide suspension slurry to print out a cemented carbide part blank with a gradient structure.

[0094] (4) Drying, degreasing and sintering: The cemented carbide component blank is dried at 80-120°C to evaporate and remove the residual solvent acetone; then, the cemented carbide component blank is kept at 400-800°C for 1-4 hours under a protective atmosphere to decompose and remove the organic matter in the cemented carbide component blank, and finally sintered at a temperature range of 1280-1480°C to obtain a dense gradient structure cemented carbide component.

[0095] As mentioned above, this application uses cemented carbide suspension slurries with different hard phase contents as raw materials, establishes a gradient structure cemented carbide component model through three-dimensional modeling software, and uses a multi-nozzle 3D printing device to selectively spray and deposit cemented carbide suspension slurries with different hard phase contents layer by layer according to the model data, and at the same time uses ultraviolet light to trigger the curing reaction of the photosensitive resin in the suspension slurry, so as to print a gradient structure cemented carbide blank, and finally obtain a cemented carbide component with a gradient structure after degreasing and sintering. This method greatly reduces the requirements of 3D printing technology for powder morphology and fluidity while maintaining the characteristics of 3D printing technology such as free forming ability, 100% material utilization rate, and rapid forming, and realizes the optimal design and low-cost printing of "double high" performance gradient structure cemented carbide components.

[0096] Compared with traditional methods, the preparation method of cemented carbide parts provided in this application can not only directly form cemented carbide parts with complex shapes, but also achieve precise control of the gradient structure of the parts, thereby optimizing the appearance and internal gradient structure of the cemented carbide parts and obtaining "double high" mechanical properties of high hardness and high toughness.

[0097] In addition, the present application also provides an application of the above-mentioned cemented carbide parts, which can be used to process mechanical tools. Accordingly, the present application also protects mechanical tools containing the above-mentioned cemented carbide parts. In an optional embodiment, the mechanical tools may include cutting tools, geological mining tools or wear-resistant parts, etc.

[0098] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0099] Example 1

[0100] This embodiment takes gradient structure high manganese steel bonded cemented carbide as an example. Three high manganese steel bonded cemented carbide powders with different TiC (hard phase) contents were designed and prepared, and the chemical compositions are shown in Table 1.

[0101] Table 1 Composition of high manganese steel bonded cemented carbide powder

[0102]

[0103] The preparation method of gradient structure high manganese steel bonded cemented carbide is as follows, and its flow chart is as follows Figure 1 As shown:

[0104] (1) Preparation of high manganese steel bonded cemented carbide suspension slurry. Figure 1 (a) indicates.

[0105] The compositions of the three cemented carbide suspension slurries are shown in Table 2. The components are evenly mixed using a ball mill to prepare three types of suspension slurries of high manganese steel-bonded cemented carbide with different TiC contents: I, II, and III.

[0106] Table 2 High manganese steel bonded cemented carbide suspension slurry

[0107]

[0108] (2) Design of the gradient structure 3D model. Figure 1 (b) indicates.

[0109] A steel-bonded carbide part model with a gradient structure was designed and constructed. The top of the part is composed of 40wt% TiC-high manganese steel composite material; the TiC content in the middle to the bottom changes from 30wt% to 20wt% to obtain excellent performance of high hardness and wear resistance at the top and high strength and toughness at the bottom. The linear size of the three-dimensional model was enlarged by 116%, and layered slice processing was performed to generate printing data.

[0110] (3) Multi-nozzle 3D printing Figure 1 (c) indicates.

[0111] According to the printing data, a gradient structure steel bonded cemented carbide part blank 4 is printed through a multi-nozzle 3D printing system (also called a multi-nozzle 3D printing device). Specifically, the cemented carbide suspension slurry feeding system 1 is connected to the multi-nozzle printing system 2 through a pipeline, and the ultraviolet light generator 3 is configured to irradiate ultraviolet light to the deposition location during the printing process.

[0112] (4) Drying, degreasing and sintering. Figure 1 (d) and Figure 1 (e) means, among which, Figure 1 (d) represents the drying process, Figure 1 (e) shows the debinding and sintering process.

[0113] The gradient structure pick blank is dried at 40°C for 2 hours to evaporate and remove the residual solvent acetone; then, under a protective atmosphere, the part blank is kept at 400°C for 4 hours to decompose and remove the organic matter therein, and finally sintered at 1280°C for 2.5 hours to obtain a dense cemented carbide part with a gradient structure, whose porosity is less than 0.02%.

[0114] The sintered parts have a distinct gradient structure, with the TiC content varying from 20wt% to 30wt% to 40wt% from the top to the bottom (e.g. Figure 2 Specifically, from top to bottom, there are 40wt% TiC alloy layer 5, 30wt% TiC alloy layer 6 and 20wt% TiC alloy layer 7, which is consistent with the design concept and the three-dimensional model. The thickness of the 20wt% TiC alloy layer 7 is 30mm, the thickness of the 30wt% TiC alloy layer 6 is 75mm, and the thickness of the 40wt% TiC alloy layer 5 is 70mm. The spatial gradient distribution of TiC (hard phase) of the sintered sample is shown in Figure 3 As shown, the XRD curve is Figure 4 As shown. Accordingly, the mechanical properties with gradient changes were obtained: density 6.79-6.5-6.22g / cm 3 , hardness 45.6-52.8-59.9HRC (such as Figure 5 As shown), flexural strength 2122.7-1711.3-1470.3MPa, impact toughness 19.14-13.35-9.75J / cm 2 (like Figure 6 As shown in Figure 3, the wear resistance increases with the increase of TiC.

[0115] Example 2

[0116] This embodiment takes a gradient structure WC-Co cemented carbide as an example. Two cemented carbide powders with different WC (hard phase) contents are designed and prepared, and the chemical compositions are shown in Table 3.

[0117] Table 3 Composition of high manganese steel bonded carbide powder

[0118]

[0119]

[0120] The preparation method of gradient structure WC-Co cemented carbide is as follows:

[0121] (1) Preparation of cemented carbide suspension slurry with different WC contents

[0122] As shown in Table 4, the mixture was evenly mixed by ball milling to prepare suspension slurries of cemented carbide with different WC contents, IV and V.

[0123] Table 4 Composition of cemented carbide suspension slurry

[0124]

[0125] (2) Design of gradient structure model

[0126] The designed gear model has a double-layer structure, and the hard phase content increases from the inner layer to the outer layer to obtain gradient performance of high hardness and wear resistance in the outer layer and high toughness in the inner layer.

[0127] (3) Multi-nozzle 3D printing

[0128] Gradient structure cemented carbide gears (such as Figure 7 The hard phase content increases gradually from the inner layer to the outer layer, which is consistent with the three-dimensional model.

[0129] (4) Drying, degreasing and sintering

[0130] The gradient structure gear blank was dried at 80°C for 1 hour to evaporate the residual solvent; then, the pick blank was kept at 800°C for 1 hour under a protective atmosphere to decompose and remove the organic matter therein, and finally sintered at 1480°C for 1 hour to obtain a dense (porosity < 0.02%) cemented carbide gear with a gradient structure, the microstructure of which is shown in FIG. Figure 8 As shown. The outer layer of the gradient structure gear is a 0.2mm thick 90wt% WC-Co hard wear-resistant layer 9, and the inner layer (core) is a 20wt% WC-Co high toughness layer 8 with a width of about 69mm. From the outer layer to the inner layer, the hardness value changes from 91HRA to 85HRA, the bending strength increases from 2820MPa to 3200MPa, and the impact toughness increases from 2.5J / cm 2 -10.3J / cm 2 Changes, with gradient properties of high hardness and wear resistance in the outer layer and high toughness in the inner layer (such as Fig. 9 shown).

[0131] Example 3

[0132] The difference between this embodiment and embodiment 1 is that polyurethane acrylate is used as the photosensitive resin, tripropylene glycol diacrylate is used as the active diluent, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide photoinitiator is used as the photoinitiator to prepare three suspension slurries of high manganese steel-bonded cemented carbide with different TiC contents VI, VII, and VIII (as shown in Table 5).

[0133] Table 5 Composition of cemented carbide suspension slurry

[0134]

[0135] Similarly, through gradient structure design, multi-nozzle 3D printing and drying, degreasing and sintering, a dense cemented carbide part with a gradient structure similar to that in Example 1 was obtained, and the same gradient-changing mechanical properties were obtained.

[0136] Comparative Example 1

[0137] Conventional powder metallurgy methods (mixing hard phase powder and bonding metal powder evenly, pressing into shape and sintering at 1350-1480°C) produce uniformly structured cemented carbide parts, in which the hard phase is evenly distributed in the bonding metal matrix, such as Fig.10 However, the wear resistance and toughness cannot be achieved by the uniform structure cemented carbide. The performance comparison between the uniform structure cemented carbide and the gradient structure cemented carbide prepared in Example 2 is shown in Table 6.

[0138] Table 6 Performance comparison of the gradient structure cemented carbide prepared in Example 2 and the powder metallurgy uniform structure parts

[0139]

[0140] Comparative Example 2

[0141] The steps are similar to those in Example 1, except that the green body formed by multi-nozzle printing is sintered at 1200°C, and a dense gradient structure cemented carbide component cannot be obtained. Fig.11 As shown, it contains a large number of pores.

[0142] In summary, the present application provides cemented carbide suspension slurries with different hard phase contents and a gradient structure cemented carbide component prepared using the cemented carbide suspension slurry and a preparation method thereof. The 3D printing technology is combined with the designability of cemented carbide materials to transform the design concept into a composition / structure with gradient changes in space, so that the performance of the component has a corresponding gradient change in space.

[0143] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a cemented carbide component, characterized in that: The cemented carbide component is obtained by sintering a cemented carbide component blank formed by 3D printing; The cemented carbide component has at least two cemented carbide layers, each of which contains a hard phase and a bonding phase, and the hard phase and the bonding phase in the at least two cemented carbide layers are respectively gradient-changed along the setting direction of the cemented carbide layers; Along the setting direction, the content of the hard phase changes gradually within the range of 20-90 wt%, and the content of the bonding phase changes gradually within the range of 80-10 wt%; The hard phase is formed by a refractory metal hard compound, and the bonding phase is formed by a bonding metal or a bonding alloy; the refractory metal hard compound is at least one of TiC, WC, Ti(C,N) and Cr3C2; the bonding metal includes at least one of Ni, Mo, Co, Fe and alloys thereof; The cemented carbide component blank is obtained by: spraying and depositing a cemented carbide suspension slurry containing different contents of the hard phase according to 3D printing data, and irradiating with ultraviolet light during the spraying and deposition process; The cemented carbide suspension slurry contains, by volume percentage, 50-62% of cemented carbide powder, 15-20% of photosensitive resin, 10-15% of active diluent, 2-5% of photoinitiator, 5-10% of solvent, 0.5-2% of dispersant and 0.1-0.5% of defoamer; the cemented carbide powder contains 20-90 wt% of refractory metal hard compound, and the remainder is bonding metal or bonding alloy.

2. The preparation method according to claim 1, characterized in that: The porosity of each cemented carbide layer is less than 0.02%.

3. The preparation method according to claim 1, characterized in that: The number of the hard alloy layers is 3, and the 3 hard alloy layers are arranged in sequence from bottom to top.

4. The preparation method according to claim 3, characterized in that: The thickness of each cemented carbide layer is not less than 0.2 mm.

5. The preparation method according to claim 4, characterized in that: The thickness of the first hard alloy layer at the bottom is 28-32 mm; the thickness of the third hard alloy layer at the top is 68-72 mm; the thickness of the second hard alloy layer between the first hard alloy layer and the third hard alloy layer is 74-76 mm.

6. The preparation method according to claim 1, characterized in that: The number of the hard alloy layers is 2, and the 2 hard alloy layers are arranged in sequence from the inside to the outside.

7. The preparation method according to claim 6, characterized in that: The width of the first hard alloy layer located in the inner layer is 68-70 mm; the thickness of the second hard alloy layer located in the outer layer is 0.15-0.25 mm.

8. The preparation method according to claim 1, characterized in that: The particle size of cemented carbide powder is 2-40 μm.

9. The preparation method according to claim 1, characterized in that: The photosensitive resin includes at least one of epoxy acrylate resin, bisphenol A epoxy acrylate and polyurethane acrylate.

10. The preparation method according to claim 1, characterized in that: The reactive diluent includes at least one of dipropylene glycol diacrylate, 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

11. The preparation method according to claim 1, characterized in that: The photoinitiator includes at least one of 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-2-methylphenylacetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and isooctyl p-N,N-dimethylaminobenzoate.

12. The preparation method according to claim 1, characterized in that: The solvent includes at least one of acetone, ethanol and chloroform.

13. The preparation method according to claim 1, characterized in that: The dispersant includes at least one of oleic acid, DP310 polymer dispersant and EFKA-5064 dispersant.

14. The preparation method according to claim 1, characterized in that: The defoaming agent includes at least one of n-butanol and polyether-modified silicone oil.

15. The preparation method according to claim 1, characterized in that: The sintering is carried out at 1280-1480°C.

16. The preparation method according to claim 1, characterized in that: Before sintering, the hard alloy component blank is degreased.

17. The preparation method according to claim 1, characterized in that: Degreasing is carried out under protective atmosphere at 400-800 ℃ for 1-4 h.

18. The preparation method according to claim 1, characterized in that: Before degreasing, the hard alloy component blank is dried.

19. The preparation method according to claim 1, characterized in that: Drying is carried out at 40-80°C.

Citation Information

Patent Citations

  • Method for preparing WC-Co gradient hard alloy material

    CN101545058A

  • Method for molding hard alloy functionally gradient materials

    CN104874797A

  • Hard alloy with surface-layer binding-phase-rich gradient structure and preparation method thereof

    CN111378885A

  • Hard alloy part and mechanical tool

    CN215356178U

  • High strength hard alloy and method of preparing the same

    US20070110607A1